Penegakan Disiplin Positif Sebagai Upaya Meminimalisir Hukuman Fisik Dan Non Fisik - Ernawati, Ernawati; Munasir, Munasir; Anwar, Rosihan; Nurhadi, Hafidin; Nuriana, Didin (Jurnal Ilmiah Wahana Pendidikan, 2024)
Violence against children has been at a very high rate for the past two years, even though it has decreased in one year, violence against children in the family environment still occupies the highest position followed by violence in the school environment. So far, it has been revealed from several studies that the cause of violence against children perpetrated by parents is the perception of parents about violence against children. Parents' perceptions related to enforcing discipline in children are always related to punishments that contain both physical and non-physical violence. So far, punishments often target the physical in the form of slaps, pinches, or taunts, verbal punishments such as threats, insinuations, and insults, physical stimulus punishments in the form of glaring and sneering, and punishments that make children uncomfortable, such as standing in front of the class or running around the field at school while sun is hot. As is well known, the impact of punishment can affect cognitive development such as inability to learn language and mathematics, emotional in the form of disturbances in intrapersonal and interpersonal relationships, and socially in children such as aggressive behavior when children are attacked by other people. This study used the literature study method in the form of a study of books and positive discipline modules, as well as journals related to the implementation of positive discipline in upholding discipline in children without violence. The results of the study state that enforcing discipline in children without violence can be carried out using positive discipline methods through the seven principles of positive discipline, namely; internal awareness is not external control, logical consequence is not punishment, encouragement is not reward, connection before correction, understanding is not judgmental, self-control is not controlling others, and is both gentle and firm